Factors Influencing the Interest of Accounting Students’ Career as Public Accountant: Work Environment as Moderators - Welly, Yerisma; Loist, Christine; Wijaya, Andy; Sisca, Sisca; Sianipar, Martin Yehezkiel (E-Jurnal Akuntansi; Vol 32 No 2 (2022), 2022)
This study aims to determine the effect of financial rewards, job intrinsic values, and labor market considerations on the interests of accounting students’ career as public accountant and to determine the role of the work environment as moderators. This research is a type of quantitative research. The research sample is final year accounting major with total of 74 people. The sampling technique used was purposive sampling. The data analysis technique in this study used multiple regression analysis and moderated regression analysis. The results showed that there was a positive and significant influence between financial rewards, job intrinsic values, and labor market considerations on the interests of STIE Sultan Agung accounting students for a career as public accountant either simultaneously or partially. The work environment was not able to moderate the relationship between financial rewards, job intrinsic values and labor market considerations. Keywords: Financial Rewards; Interest; Job Intrinsic Values; Labor Market Considerations; Public Accountant.